2008
DOI: 10.1038/sc.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neurotrophin-3 on the dorsal root transitional zone following injury

Abstract: Study design: Morphological and Stereological assessment of the dorsal root transitional zone (DRTZ) following complete crush injury, using light microscopy (LM) and transmission electron microscopy (TEM). Objectives: To assess the effect of exogenous neurotrophin-3 (NT-3) on the response of glial cells and axons to dorsal root damage. Setting: Department of Anatomy, University College Cork, Ireland and Department of Physiology, UMDS, University of London, UK. Methods: Cervical roots (C6-8) from rats which had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Studies found that NT-3 can promote the differentiation of neural stem cells into neurons and oligodendrocytes, while there is relatively little differentiation into astrocytes [ 26 28 ]. Ramu et al found that after 4 weeks of NT-3 treatment, the injured contralateral cerebral cortex, thalamus, caudate nucleus, hippocampus and other peripheral gray matter of rats showed strong signals [ 29 ], Hanna-Mitchell et al found that NT-3 reduced neuronal apoptosis and promoted axon growth in the central nervous system [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that NT-3 can promote the differentiation of neural stem cells into neurons and oligodendrocytes, while there is relatively little differentiation into astrocytes [ 26 28 ]. Ramu et al found that after 4 weeks of NT-3 treatment, the injured contralateral cerebral cortex, thalamus, caudate nucleus, hippocampus and other peripheral gray matter of rats showed strong signals [ 29 ], Hanna-Mitchell et al found that NT-3 reduced neuronal apoptosis and promoted axon growth in the central nervous system [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike BDNF, it is effective at preventing atrophy of ascending spinal sensory neurons (Bradbury et al, 1998;Shibayama et al, 1998), and at instigating regeneration of sensory axons into and within the spinal cord (Bradbury et al, 1999;Oudega and Hagg, 1999;Ramer et al, 2000Ramer et al, , 2002. Intrathecal NT-3 also reduces the astrogliotic and microglial responses to spinal deafferentation while preserving or increasing the amount of oligodendroglial tissue (Hanna-Mitchell et al, 2008). Based on demonstrations of NT-3's suppressive actions on sodium channels linked to neuropathic pain (WilsonGerwing et al, 2005(WilsonGerwing et al, , 2008, it is tempting to speculate that the combination of NT-3's effects may warrant its inclusion in an eventual therapy.…”
Section: Neurotrophic Factorsmentioning
confidence: 95%
“…Growth factor-mediated growth of dorsal root axons appears to act on intracellular pathways, which at least in part share those implicated in the conditioning lesion response [ 68 ], although simultaneous effects on non-neuronal cells at the DREZ may also occur [ 69 ]. Importantly, there appears to be a limited time window for neurotrophin-mediated entry of regenerating dorsal root axons since just a short delay of treatment fails to support spinal cord ingrowth [ 70 ].…”
Section: Overcoming the Limited Regenerative Competence After Dorsal Root Injurymentioning
confidence: 99%